The equation that you should use to solve this is (13 + 1/4) - (6 + 2/3) = 6 and 7/12
Answer: It would be y=2x.
first we need to get rid of the ( ) so that we can see what the question really says
(3x³-5x² - 7+ 4x4) + (9x4 - 10x² - 5x³ + 3)
= 3x³-5x²-7+4x⁴+9x⁴-10x²-5x³+3
now all we need to do is add up the numbers with the same x's
<em>3x³</em>-5x²-7<u>+4x⁴+9x⁴</u>-10x²<em>-5x³</em>+3
= 13x⁴-2x³-15x²-4
Answer:
X = 4
Step-by-step explanation:
In the equation add 3 to both sides of the equation
1/2x-3+3=2-3/4x+3
Simplify
1/2x = -3/4x + 5
Add 3/4x to both sides
1/2x + 3/4x = -3/4x + 5 + 3/4x
Simplify
5/4x=5 Multiply both sides by 5
5x=20 divide both sides by 5
5x divided by 5 and 20 divided by 5
=4
Answer:
The inverse function is f(x) = x^2 - 3
Step-by-step explanation:
To find the inverse of any function, start by switching the x and f(x) values.
f(x) = √(x + 3)
x = √(f(x) + 3)
Now solve for the new f(x). The result will be your inverse function.
x = √(f(x) + 3)
x^2 = f(x) + 3
x^2 - 3 = f(x)